Clinical characteristics and course of dying in patients with amyotrophic lateral sclerosis withdrawing from long-term ventilation. Issue 1 (2nd January 2017) - Kettemann, Dagmar; Funke, Andreas; Maier, André; Rosseau, Simone; Meyer, Robert; Spittel, Susanne; Münch, Christoph; Meyer, Thomas
Abstract: Non-invasive ventilation (NIV) or tracheotomy with invasive ventilation (TIV) are treatment options in ALS. However, a proportion of patients receiving long-term ventilation decide to have it withdrawn. The objective of this study was to analyse the clinical characteristics and palliative approaches in ALS patients withdrawing from long-term ventilation (WLTV). In a cohort study, two different palliative concepts in WLTV were studied: (1) augmented symptom control (ASC; sedation not intended) in patients with ventilator-free tolerance; (2) continuous deep sedation (CDS; sedation intended) in patients without ventilator-free tolerance. Results showed that WLTV was realised in 49 ALS patients (NIV = 13; TIV = 36). Mean daily ventilation was 23.4 h. The ALS Functional Rating Scale (ALSFRS-R) was low (5.6 of 48). Forty-one per cent of patients ( n  = 20) presented with ophthalmoplegia. ASC was performed in 20 patients, CDS in 29 patients. The mean time to death following disconnection was 32 (0.3–164) h during ASC and 0.3 (0.2–0.6) h in CDS. In conclusion, a low ALSFRS-R, high incidence of ophthalmoplegia and extended ventilator dependency were found before WLTV. The presence or absence of ventilator-free tolerance determined the approach to the management of symptoms, the setting for immediate end-of-life care and the course of dying in WLTV.